Sonographic measurement of normal plantar fascia thickness in healthy nepalese population - Dhakal, Gaurav Raj; Parajuli, Nirajan Prasad; Joshi, Kirti Subas; Shrestha, Rohit; Sherchan, Binod (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
BACKGROUND: Plantar fascitis is one of the commonest causes of heel pain. Thickening of plantar fascia is the most consistent sonological finding in plantar fasciitis. Objective: To estimate normal plantar fascia thickness in healthy Nepalese volunteers and evaluate its relationship with age, sex, height, weight and body mass index (BMI). METHODS: The plantar fascia thickness was measured at 5mm distal to its insertion into the calcaneus using 10 MHz linear array transducer. Total 700 feet of 350 healthy volunteers were evaluated in our study. Physical examination was also performed to assess height, weight and BMI. RESULTS: The mean plantar fascia thickness among entire population, male subjects, female subjects, right side and left side were respectively 2.39±0.37 (Range 1.4-3.6; 95% confidence interval=2.36-2.42); 2.47±0.37 (Range 1.4-3.6; 95% confidence interval =2.43-2.51); 2.32±0.35 (Range 1.4-3.5; 95% confidence interval =2.28-2.36); 2.39±0.36 (Range 1.4-3.6; 95% confidence interval =2.35-2.43) and 2.40±0.37 (Range 1.4-3.5; 95% confidence interval of 2.36-2.44). The mean was significantly higher in men than in women (p <0.05) but similar in left and right feet (p>0.05). Amongst age, sex, weight, height and body mass index; only age significantly co-related with the plantar fascia thickness. CONCLUSION: The mean plantar fascia thickness was 2.39±0.37mm. The mean is significantly higher in men than in women but similar in both feet. Sex, weight, height and BMI are not significantly related to the thickness. Age is the single most determinant factor of plantar fascia thickness. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.37-44